A PERIOD3 variable number tandem repeat polymorphism modulates melatonin treatment response in delayed sleep‐wake phase disorder. Issue 4 (16th September 2020) - Magee, Michelle; Sletten, Tracey L.; Murray, Jade M.; Gordon, Christopher J.; Lovato, Nicole; Bartlett, Delwyn J.; Kennaway, David J.; Lockley, Steven W.; Lack, Leon C.; Grunstein, Ronald R.; Archer, Simon N.; Rajaratnam, Shantha M.W.; et al.
Abstract: We examined whether a polymorphism of the PERIOD3 gene ( PER3; rs57875989 ) modulated the sleep‐promoting effects of melatonin in Delayed Sleep‐Wake Phase Disorder (DSWPD). One hundred and four individuals (53 males; 29.4 ±10.0 years) with DSWPD and a delayed dim light melatonin onset (DLMO) collected buccal swabs for genotyping (PER3 4/4 n = 43; PER3 5 allele [heterozygous and homozygous] n = 60). Participants were randomised to placebo or 0.5 mg melatonin taken 1 hour before desired bedtime (or ~1.45 hours before DLMO), with sleep attempted at desired bedtime (4 weeks; 5‐7 nights/week). We assessed sleep (diary and actigraphy), Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), Patient‐Reported Outcomes Measurement Information System (PROMIS: Sleep Disturbance, Sleep‐Related Impairment), Sheehan Disability Scale (SDS) and Patient‐ and Clinician‐Global Improvement (PGI‐C, CGI‐C). Melatonin treatment response on actigraphic sleep onset time did not differ between genotypes. For PER3 4/4 carriers, self‐reported sleep onset time was advanced by a larger amount and sleep onset latency (SOL) was shorter in melatonin‐treated patients compared to those receiving placebo ( P  = .008), while actigraphic sleep efficiency in the first third of the sleep episode (SE T1) did not differ. For PER3 5 carriers, actigraphic SOL and SE T1 showed a larger improvement with melatonin ( P  < .001). Melatonin improved ISI ( P  = .005), PROMIS sleep disturbance ( P  < .001) and sleep‐related impairment ( P  = .017), SDS ( P  = .019), PGI‐C ( P  = .028) and CGI‐C ( P  = .016) in PER3 4/4 individuals only. Melatonin did not advance circadian phase. Overall, PER3 4/4 DSWPD patients have a greater response to melatonin treatment. PER3 genotyping may therefore improve DSWPD patient outcomes.